2014 14th International Conference on Hybrid Intelligent Systems 2014
DOI: 10.1109/his.2014.7086168
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling of blood flow through an eccentric catheterized artery: A practical approach for a complex system

Abstract: In this research a two dimensional, single phase, and isothermal model is developed to investigate the effects of eccentric catheterization on blood flow characteristics in a tapered and stenosis artery which is complex system. The model conducted by assuming that the blood is as Newtonian and incompressible fluid and the temperature effects are also neglected. The results clearly show that the axial velocity and the magnitude of the wall shear stress distribution are higher for eccentric catheter than that fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The pulse wave signal and ECG signal are combined to measure the pulse wave conduction time. The pulse wave signal includes a number of harmonic syntheses and is highly impacted by the surrounding environment [26] . However, the ECG signal acquisition device is a flexible electrode, which adheres tightly to the human body and is easy to relocate.…”
Section: Blood Pressure Diagnosis Algorithmmentioning
confidence: 99%
“…The pulse wave signal and ECG signal are combined to measure the pulse wave conduction time. The pulse wave signal includes a number of harmonic syntheses and is highly impacted by the surrounding environment [26] . However, the ECG signal acquisition device is a flexible electrode, which adheres tightly to the human body and is easy to relocate.…”
Section: Blood Pressure Diagnosis Algorithmmentioning
confidence: 99%
“…[1][2][3][4] The beat-to-beat BP data reveal a great deal of information about the dynamic features of cardiovascular control mechanisms, 5 which is significant for both disease prevention and clinical diagnosis. [6][7][8] At present, most of the clinical approaches are cuff based, which is uncomfortable during the inflation process. Therefore, cuff-less technique is much more desirable.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of electronics technology miniaturization [1], the monitoring of human health is gaining more and more attention. One public health report in 2010 showed that almost 1 in every 4 deaths every year in the United States is due to heart disease [2].…”
mentioning
confidence: 99%